Assessing Public Willingness to Pay for Earthquake Disaster Insurance in Yogyakarta, Indonesia: An Economic Valuation Using Contingent Valuation Method - Permadi, Wisnu Yudhistira Nur; Saptutyningsih, Endah (Journal of Economics Research and Social Sciences, 2024)
Jetis District, Bantul Regency, is the area that experienced the most casualties and the worst damage to buildings after the earthquake on May 27, 2006. One of the worst earthquakes of the twenty-first century was the 5.9-magnitude one. The existence of insurance premiums that people are willing to pay is very necessary as an alternative form of post-disaster risk mitigation effort. The aim of this research is to determine the willingness to pay disaster mitigation insurance premiums and the influence of the independent variables. An EWTP of IDR 62,700 (USD 4,04) was obtained using the dichotomous choice method for 20 community samples. This research was conducted on 274 respondents using the contingent valuation method. This research uses logistic regression analysis. The research results show that the variables age, number of dependent family members, educational attainment, income, length of residence, and risk aversion have a significant influence on willingness to pay disaster mitigation insurance premiums.